Pemberdayaan Pendidikan Usia Dini Aisyiyah Kasihan melalui Pelatihan Pembuatan Video Pembelajaran dan Manajemen Pembelajaran Berbasis Internet: Empowerment of Aisyiyah’s Early Childhood Education through Training on Making Internet-Based Learning Videos and Learning Management - Raharjo, Arif Budi; Bachtiar, Asep Purnama (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Since the COVID-19 pandemic hit the Indonesian people, the Branch of Aisyiyah Kasihan Early Childhood Education (PAUD) has implemented PJJ (distance learning) as a learning model. However, PJJ has not been able to be implemented optimally due to two things: first, the application for making learning videos has not been used optimally by PAUD teachers. Second, the use of the Internet network has yet to be maximized in learning management. This service program aims to optimize PJJ by improving teacher skills in making learning videos and internet-based learning management. The method used is FGD, training, and assistance using the Filmora, Google Drive, and YouTube Chanel applications. The results indicate that PJJ is implemented better because complete and interesting learning videos and internet-based learning management management support it. Second, digital literacy in teachers has increased after having new experiences and skills in making learning videos that are more interesting and have a school trademark, and principals use the internet more as a learning management instrument.